"Science" and "art" as ways of knowing in school education in Nepal for an inclusive learning environment - Binod Prasad Pant; Bal Chandra Luitel; Birgitte Bjønness; Sigrid Gjøtterud (Springer, 2023)
Abstract For several years, science and art have been viewed as separate entities in school education in Nepal. The dominant discourse on science was regulated by Western Modern Worldview (WMW), assuming that seeking universal truth should be the central aim of the exploration. In this article, science refers to the absolutist/rigid nature of different disciplines (such as Science and Mathematics) from the perspectives of Newtonian science, whereas art is viewed from three dimensions; literary arts (i. e. narratives, storing), visual arts (i.e., images, painting, sculpture) and performing arts (i.e., role play, drama). This paper argues that science and arts, as ways of knowing, should be taken as complements of each other. This literature-based argumentative paper also incorporates the lead author's experiences using art as/for pedagogical approaches in collaboration with schoolteachers. At the same time, the authors also argue the role of critical reflection to acknowledge both science and art as epistemology. The authors have used Dewey's perspectives on the roles of art for experiencing in education. Also, the notion of Mezirow's Transformative Learning is helpful as an influential lens to showcase the ever-changing thoughts in the transformation continuum. To set the context for the argumentation, the authors discussed the existing Nepali school education system, focused on curricula and pedagogical perspectives. The paper is helpful for teachers, teacher educators, and researchers to critically reflect on their own beliefs and practices in terms of viewing the different perspectives on STEM subjects and the inseparable relationship of science and art for knowledge generation and pedagogical application.